Photodegradation Kinetics of Aflatoxin B1 in Solvent - Liu, Ruijie; Chang, Ming; Jin, Qingzhe; Huang, Jianhua; Liu, Yuanfa; Wang, Xingguo (Asian Journal of Chemistry, 2012)
A photodegradation study of aflatoxin B1 (AFB1) in acetonitrile solution was performed under UV irradiation at different aflatoxin B1 initial concentrations, UV irradiation intensities and wavelengths. The effect of UV intensity and wavelengths on the aflatoxin B1 photodegradation ratio is dominative, comparing to aflatoxin B1 initial concentration. The photodegradation of aflatoxin B1 was proved to follow first-order reaction kinetics (R2 ³ 0.99). The aflatoxin B1 photodegradation rate under various conditions was lower following the order: v(800 μw/cm2) > v(400 μw/cm2) > v(200 μw/cm2) and v(UV-C) > v(UV-A) > v(VIS). This study reports the photodegradation behaviour-kinetics in solvent model, providing clues to the study of the photodegradation mechanism of aflatoxin B1 in real food medium and the UV method applied in practical decontamination of aflatoxin B1 in food.